Robustness and applicability of transcription factor and pathway analysis tools on single-cell RNA-seq data - Holland, Christian H.; Tanevski, Jovan; Perales-Patón, Javier; Gleixner, Jan; Kumar, Manu P.; Mereu, Elisabetta; Joughin, Brian A.; Stegle, Oliver; Lauffenburger, Douglas A.; Heyn, Holger; Szalai, Bence; Sáez Rodríguez, Julio (Genome biology, 2020)
Many functional analysis tools have been developed to extract functional and mechanistic insight from bulk transcriptome data. With the advent of single-cell RNA sequencing (scRNA-seq), it is in principle possible to do such an analysis for single cells. However, scRNA-seq data has characteristics such as drop-out events and low library sizes. It is thus not clear if functional TF and pathway analysis tools established for bulk sequencing can be applied to scRNA-seq in a meaningful way.
Gesehen am 02.04.2020